Post COVID-19 syndrome and new onset diseases: a prospective observational study - Nitin Sinha; Mahinder Pal Singh Chawla; Desh Deepak; Amit Suri; Piyush Jain; Ankit Agarwal; Manoj Kumar Bhakhar (Singapore Medical Journal)
Introduction: The National Institute of Health and Care Excellence (NICE) has defined the terms, ‘acute coronavirus disease 2019’ (COVID-19), ‘ongoing symptomatic COVID-19’ and ‘post-COVID-19 syndrome’, with the latter two described as having persistent symptoms after the onset of COVID-19 symptoms for 4–12 weeks and >12 weeks, respectively. Persistent symptoms can either be due to the after-effects of COVID-19 or new-onset diseases after acute COVID-19. All symptoms observed beyond 4 weeks after the onset of COVID-19 need not be present at the time of onset. Previous studies on persistent post-COVID-19 symptoms have not mentioned new-onset diseases after acute COVID-19, and only a select few studies have discussed such new-onset symptoms. Methods: Ninety-five patients who attended the post-COVID-19 clinic completed the requisite follow-up till 16 weeks after COVID-19 symptom onset. Data was recorded on a predesigned proforma. Necessary investigations were conducted to rule out any other cause of persistent symptoms. Results: Fatigue (62.1%), breathlessness (50.5%) and cough (27.4%) were the most common symptoms present beyond 4 weeks after the onset of COVID-19 symptoms. Forty-nine (51.57%) patients developed post-COVID-19 syndrome — their severity of symptoms (odds ratio [OR] 17.77) and longer duration of hospital stay (OR 1.095) during acute disease were significantly associated with the development of post-COVID-19 syndrome. During follow-up, 25 patients developed new-onset symptoms, such as diabetes mellitus, hypertension and idiopathic tachycardia. Conclusion: Patients can have persistent symptoms, new-onset symptoms and new-onset diseases after recovery from acute COVID-19.